A conceptual model of the microwave channel of information leakage by the power supply circuit - Козловський, Валерій Валерійович; Лисенко, Роман Михайлович (Ukrainian Information Security Research Journal, 2013)
For the construction of the microwave filter devices to prevent information leakage on the supply lines should take into account the impact of external screens. Existing methods for the synthesis filtering devices are based on the mathematical model the two-wire transmission line, excluding the effect of shielding the outer envelope. As a result, the frequency response function of the filter is different from the experimental, which leads to deterioration in the band rejection filter. Proposed as a conceptual mathematical model of the filter element model coupled transmission line. The conceptual model takes into account the effect of shielding the outer shell and increases the accuracy of calculating the filtration devices in the power supply circuit.